Altered interregional molecular associations of the serotonin transporter in attention deficit/hyperactivity disorder assessed with PET. Issue 2 (22nd October 2016) - Vanicek, Thomas; Kutzelnigg, Alexandra; Philippe, Cecile; Sigurdardottir, Helen L.; James, Gregory M.; Hahn, Andreas; Kranz, Georg S.; Höflich, Anna; Kautzky, Alexander; Traub‐Weidinger, Tatjana; Hacker, Marcus; Wadsak, Wolfgang; et al.
Abstract: Altered serotonergic neurotransmission has been found to cause impulsive and aggressive behavior, as well as increased motor activity, all exemplifying key symptoms of ADHD. The main objectives of this positron emission tomography (PET) study were to investigate the serotonin transporter binding potential (SERT BPND ) in patients with ADHD and to assess associations of SERT BPND between the brain regions. 25 medication‐free patients with ADHD (age ± SD; 32.39 ± 10.15; 10 females) without any psychiatric comorbidity and 25 age and sex matched healthy control subjects (33.74 ± 10.20) were measured once with PET and the highly selective and specific radioligand [ 11 C]DASB. SERT BPND maps in nine a priori defined ROIs exhibiting high SERT binding were compared between groups by means of a linear mixed model. Finally, adopted from structural and functional connectivity analyses, we performed correlational analyses using regional SERT binding potentials to examine molecular interregional associations between all selected ROIs. We observed significant differences in the interregional correlations between the precuneus and the hippocampus in patients with ADHD compared to healthy controls, using SERT BPND of the investigated ROIs ( P < 0.05; Bonferroni corrected). When correlating SERT BPND and age in the ADHD and the healthy control group, we confirmed an age‐related decline in brain SERT binding in the thalamus and insula ( R 2 = 0.284, R 2 = 0.167, P s < 0.05; Bonferroni corrected). The results show significantly different interregional molecular associations of the SERT expression for the precuneus with hippocampus in patients with ADHD, indicating presumably altered functional coupling. Altered interregional coupling between brain regions might be a sensitive approach to demonstrate functional and molecular alterations in psychiatric conditions. Hum Brain Mapp 38:792–802, 2017 . ©2016 Wiley Periodicals, Inc.